2010
DOI: 10.1073/pnas.1008775108
|View full text |Cite
|
Sign up to set email alerts
|

Non–cell-autonomous factor induces the transition from excitatory to inhibitory GABA signaling in retina independent of activity

Abstract: During development, the effect of activating GABA A receptors switches from depolarizing to hyperpolarizing. Several environmental factors have been implicated in the timing of this GABA switch, including neural activity, although these observations remain controversial. By using acutely isolated retinas from KO mice and pharmacological manipulations in retinal explants, we demonstrate that the timing of the GABA switch in retinal ganglion cells (RGCs) is unaffected by blockade of specific neurotransmitter rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 62 publications
(87 reference statements)
1
26
0
Order By: Relevance
“…GABA and glycine receptors are initially excitatory, but become inhibitory as the retina reaches maturity [14], [15] due to a change in the chloride equilibrium potential which coincides with an up-regulation of the chloride extruder KCC2 [59]. This is a gradual process, occuing throughout the course of stage II and stage III waves [14], [60]. In ferret, it has been shown that GABAARs become inhibitory after P18, while glycine receptors become inhibitory by P21 [10], ages where stage III waves are still active.…”
Section: Discussionmentioning
confidence: 99%
“…GABA and glycine receptors are initially excitatory, but become inhibitory as the retina reaches maturity [14], [15] due to a change in the chloride equilibrium potential which coincides with an up-regulation of the chloride extruder KCC2 [59]. This is a gradual process, occuing throughout the course of stage II and stage III waves [14], [60]. In ferret, it has been shown that GABAARs become inhibitory after P18, while glycine receptors become inhibitory by P21 [10], ages where stage III waves are still active.…”
Section: Discussionmentioning
confidence: 99%
“…Second, acetylcholinesterase, the enzyme that degrades ACh, is increased during this time window (Hutchins et al , 1995), which would decrease the spread of ACh. Third, the action of GABA becomes hyperpolarizing a few days before the onset of glutamatergic waves (Zhang et al , 2006b; Barkis et al , 2010). Intracellular chloride is reduced as the expression of the potassium-chloride transporter KCC2 is increased in ganglion cells (Zhang et al , 2006a).…”
Section: Disassembly Of the Cholinergic Networkmentioning
confidence: 99%
“…References:(1) (Voinescu et al , 2009) (2) (Kim et al , 2000) (3) (Hinds & Hinds, 1983) (4) (Fisher, 1979) (5) (Bansal et al , 2000) (6) (Johnson et al , 2003) (7) (Xu & Tian, 2004) (8) (Barkis et al , 2010) (9) (Zheng et al , 2004) (approximate age from rabbit data)…”
Section: Figurementioning
confidence: 99%
“…They are first mediated by gap junctions (Stage I: late gestation) (Catsicas et al 1998;Bansal et al 2000;Syed et al 2004a), and then depend on cholinergic synaptic transmission (Stage II: until P9-10 in mouse) (Feller et al 1996;Sernagor & Grzywacz, 1996, 1999Catsicas et al 1998;Wong et al 1998;Bansal et al 2000;Sernagor et al 2000;Zhou & Zhao, 2000;Sernagor et al 2003;Syed et al 2004b). GABAergic signalling becomes involved in modulating waves at around P4-5 in mouse (Zhang et al 2006;Hennig et al 2011) and at these early stages is depolarizing, as it is elsewhere in the developing central nervous system (CNS) (Ben-Ari et al 2007), shifting polarity after P6 (Zhang et al 2006;Barkis et al 2010). Finally, glutamate signalling between bipolar cells takes over as the main driver of Stage III waves at around P10 in mouse (Bansal et al 2000;Zhou & Zhao, 2000;Syed et al 2004b;Blankenship et al 2009), although gap junctions between ON bipolar cells are also involved in lateral transmission (Akrouh & Kerschensteiner, 2013).…”
Section: Introductionmentioning
confidence: 99%